Interdependence : biology and beyond - Sharma, Kriti (Disability rights researcher) (Meaning systems., 2015)
"From biology to economics to information theory, the theme of interdependence is in the air, framing our experiences of all sorts of everyday phenomena. Indeed, the network may be the ascendant metaphor of our time. Yet precisely because the language of interdependence has become so commonplace as to be almost banal, we miss some of its most surprising and far-reaching implications"--